Profiling Pengukuran: Return On Invested Capital dan Intellectual Capital - Puspitasari, Elen; Widati, Listyorini Wahyu; Suwarti, Titiek; Meiranto, Wahyu (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
The research aims to compile a profile of disclosure measurement of return on invested capital and intellectual capital in banking companies with the observation period of 2020 – 2022. The sample was determined by purposive sampling that resulted in 84 observation data from 28 companies The findings of this study confirm that measuring intellectual capital with the comprehensive tool, namely Modified Value Added Capital suggests that there is a positive and significant effect on the return on invested capital. A company with a high value added intellectual capital will increase Return On Invested Capital has the ability to reinvest its profits and grow its business, resulting in long-term earnings growth and potentially higher returns for investors. The average ROIC was 7.54% (>2%), which shows that management uses funding efficiently to generate profits. Therefore, management must reinvest the surplus profits in the company to drive future growth. Keywords: Return on Invested Capital; Modified Value Added Intellectual Capital; Banking Industries.